Textiles: Concepts and Principles - Elsasser, Virginia Hencken; Sharp, Julia Ridgway (New York : Fairchild Books, 2022)
"Textiles: Concepts and Principles, Fourth Edition provides a thorough approach to the fundamentals of textiles in a readable, non-technical style. The focus is on the interrelationship of textile components to help students understand and predict textile properties and performance to ultimately choose the best textile for their final product. This book covers the global textile industry and components of textile products, summarizes laws and regulations affecting the textile industry, and looks into career possibilities, properties, care instructions, end uses of natural and manufactured fibers, yarns, fabrics, coloration and finishes, and the overall impact of textiles in the environment"--
Includes index.
Keywords: Textile fabrics; Textile fibers